2004
DOI: 10.1242/dev.01087
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis ofSox8andSox9during sex determination in the mouse

Abstract: Sex determination in mammals directs an initially bipotential gonad to differentiate into either a testis or an ovary. This decision is triggered by the expression of the sex-determining gene Sry, which leads to the activation of male-specific genes including the HMG-box containing gene Sox9. From transgenic studies in mice it is clear that Sox9 is sufficient to induce testis formation. However, there is no direct confirmation for an essential role for Sox9 in testis determination. The studies presented here a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
409
1
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(432 citation statements)
references
References 42 publications
12
409
1
10
Order By: Relevance
“…WISH analysis of Sox10 confirms expression within the male genital ridge compared to the female genital ridge at e1.5, e12.5 and e13.5, but does not suggest a strictly pre-Sertoli cell expression pattern. Although no anomalies in sex determination or differentiation are reported for SOX10 mutations, its expression within the male genital ridge during a critical period of early sex differentiation suggest that it may influence the action of other molecules such as SOX9, as is seen in the case of Sox8 (Chaboisser et al, 2004).…”
Section: Genital Ridge Expression Of Selectedmentioning
confidence: 99%
See 1 more Smart Citation
“…WISH analysis of Sox10 confirms expression within the male genital ridge compared to the female genital ridge at e1.5, e12.5 and e13.5, but does not suggest a strictly pre-Sertoli cell expression pattern. Although no anomalies in sex determination or differentiation are reported for SOX10 mutations, its expression within the male genital ridge during a critical period of early sex differentiation suggest that it may influence the action of other molecules such as SOX9, as is seen in the case of Sox8 (Chaboisser et al, 2004).…”
Section: Genital Ridge Expression Of Selectedmentioning
confidence: 99%
“…Indeed, studies have shown significant functional redundancy between these factors (Bylund et al, 2003;Cheung and Briscoe, 2003;Graham et al, 2003;Taylor and LaBonne, 2005;Kellerer et al, 2006). Within the male genital ridge, Sox8 and Sox9 gene expression are up-regulated as a consequence of Sry expression (Sekido et al, 2004) and influence male sex determination and pre-Sertoli cell differentiation (Sock et al, 2001;Takada and Koopman, 2003;Chaboisser et al, 2004;Barrionuevo et al, 2006). Several studies have shown that Sox8 and Molecular Reproduction and Development.…”
Section: Genital Ridge Expression Of Selectedmentioning
confidence: 99%
“…Heterozygous mutations of the SOX9 gene are responsible for campomelic dysplasia (Foster et al, 1994), an autosomal dominant disorder resulting in skeletal and developmental abnormalities and in frequent neonatal death because of respiratory deficiencies (Houston et al, 1983). SOX9 was then shown to be a key regulator of chondrogenesis (Akiyama et al, 2002), neurogenesis (Stolt et al, 2003), male sex determination (Chaboissier et al, 2004), neural crest development (Cheung et al, 2005) and biliary development (Antoniou et al, 2009). SOX9 is overexpressed in tumors from many origins and particularly in colon (Blache et al, 2004;Jay et al, 2005), but its role in cancer appears mostly antioncogenic.…”
Section: Introductionmentioning
confidence: 99%
“…As a transcription factor, SRY initiates a cascade of the expression of other male sex-determining genes. One of its direct targets is SOX9 (Sry-related HMG box gene 9; Kent et al, 1996, Sekido andLovell-Badge, 2008), which encodes a transcription factor that is critical to the testis differentiation process in many vertebrates (Barrionuevo et al, 2006;Chaboissier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%